Risk Factors for Bacteremia After Endoscopic Procedures in Hospitalized Patients With a Focus on Neutropenia. Issue 1 (January 2022) - Isenberg, Yoni; Zamstein, Noa; Horesh, Nurit; Chowers, Yehuda; Bar-Yoseph, Haggai
Abstract : Background: The risk for bacteremia following endoscopic procedures varies among studies. A low neutrophil count is considered as a risk factor. Objective: To assess risk factors for bacteremia following endoscopic procedures, focusing on neutropenia. Methods: This was a retrospective analysis of all inpatients undergoing endoscopic procedures between 2005 and 2018 with neutrophil count taken within 72 hours before the procedure in a tertiary center in Israel. The primary outcome was positive blood culture within 48 hours following the procedure of bacteria that was not cultured before. Risk factors for bacteremia were assessed and multivariate logistic regression models were built. In neutropenic patients, comparator groups were used to assess the risk related to the procedure and neutropenia. Results: Of 13, 168 patients included, postprocedural bacteremia was recorded in 103 (0.8%). Neutropenia, low albumin level, male gender, older age, preprocedure fever, and admitting department were associated with increased risk for bacteremia in both univariate and multivariate analyses. A multivariate model including these factors was found to be predictive of bacteremia (area under the curve 0.82; 95% confidence interval, 0.78-0.88). In neutropenic patients, the risk of postendoscopic bacteremia (4.2%) was not significantly different compared with neutropenic patients undergoing bronchoscopy (1.8%, P =0.14) or from the rate of bacteremia-to-neutropenic episodes ("background risk") in neutropenic patients in general (6.3%, P =0.33). Conclusions: Postendoscopic bacteremia is a rare event among inpatients. Although neutropenia was found to be a risk factor for bacteremia, it was not higher than the background risk in these patients. Models highly predictive of bacteremia were developed and should be validated. Abstract : Supplemental Digital Content is available in the text.